The impact of poverty, unemployment, inequality, corruption and poor governance on Niger Delta militancy, Boko Haram terrorism and Fulani herdsmen attacks in Nigeria - Olaniyi Evans; Ikechukwu Kelikume (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
The purpose of this study was to examine the impact of poverty, unemployment, inequality, corruption and poor governance on Niger Delta militancy, Boko Haram terrorism and Fulani herdsmen attacks in Nigeria. Using annual data over the period 1980-2017, this study applied fully modified OLS (FMOLS) method of estimation. The outcomes of the estimations showed that poverty, unemployment, inequality, corruption and poor governance were significant causes of Niger Delta militancy, Boko Haram terrorism and Fulani herdsmen attacks in Nigeria. In line with theories of deprivation, the study found that the various deprivations in the country led to violence and conflicts in the form of Niger Delta militancy, Boko Haram terrorism and Fulani herdsmen attacks. Thus, violence was a result of the prevailing unpleasant socio-material conditions pertaining to survival, economic deprivation, structural inequities, environmental degradation and governance deficits.
Keywords: D60; E27; H54; I31; 330; Poverty; unemployment; inequality; corruption; poor governance; Niger Delta militancy; Boko Haram terrorism; Fulani herdsmen attacks